PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE CARD SORT UNTUK MENINGKATKAN KEMAMPUAN BELAJAR SISWA PADA POKOK BAHASAN JOSUUSHI KELAS XI SMA TARUNA PEKANBARU - Lestari, Novia Lestari; Basri, M, Merri Silvia Basri Silvia; Rahayu, Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: the purpose of this research was to find out whether the use of card sort active learning strategy can improve students’ comprehension in josuushi at grate XI SMA Taruna Pekanbaru. This research was experimental research which used pretest posttest. Obyects of this research consisted of 20 science and 20 social students’ at grade XI SMA Taruna Pekanbaru.Data collection technigue used in this research was test. The researcher gave pretest and posttest to find out students’ comprehension in josuushi before and after card sort strategy was applied in teaching and learning process. The result of pretest and posttest were statistically analyted using t formula manually to know the improvement of students’ comprehension. Based on statistically analyzing data using t formula it was found that thitung 6,66 > ttabel 1,68 it means that there was asifnificant difference between students’ who taught by card sort active learning strategy and students’ who taight by conventional strategy during teaching and learning process. Keywords: Active Learning Strategy, Card Sort, Josuushi